Research on the Dilemma Faced by the Digital Economy in Promoting Urban-rural Integration and the Countermeasures to Solve it - Zhou, Dongbei (International Journal of Social Sciences and Public Administration, 2024)
At present, digital technology is becoming an important driving force to solve the "urban-rural division and one country, two policies" and promote the integrated development of urban and rural areas. This paper reviews the theoretical mechanism of digital economy to promote urban-rural integration from the aspects of urban-rural precision management, sharing economy and leapfrog development, and puts forward specific suggestions in five aspects: digital infrastructure, logistics service system, digital popularization, digital governance and financial investment.